Hip hop and Narrative Therapy in Drama Therapy: An Exploration of the ways in which Hip hop in Narrative Form can be used to Address issues of Displacement, Foster Cohesion and Conscientize a Sense of Self in Urban Adolescents - Dlamini, Sanelisiwe (University of the Witwatersrand, Johannesburg, 2024)
This research explored how Hip hop therapy and narrative therapy within the drama therapy frame can be integrated for the purposes of a psychosocial intervention for adolescents in urban Johannesburg. The research was conducted with adolescents from Organisation X, ranging between the ages of 14-18 years. This research addressed issues of displacement, violence, xenophobia, social cohesion and self-awareness in the intervention. The research methodology used a qualitative approach that is practice-based and arts-based. The design included semi- structured interviews with the four care workers at organisation X, questionnaires and creative focus groups with ten selected adolescents. This was an eight-week intervention to investigate the various ways in which Hip hop and narrative therapy can be used in the drama therapy context to address psychosocial issues affecting the adolescents. The findings of the study reflect that self-esteem of more than half the participants increased during the course of the intervention, they grew a friendlier perception towards outsiders and their sense of belonging improved during the intervention.
A research report Submitted in fulfillment of the requirements for a Masters in Drama Therapy, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Hip hop; Hip hop Therapy; Drama Therapy; Psychoeducation; Adolescent; Displacement; Cohesion; Self; Xenophobia; SDG-4: Quality education